2019
DOI: 10.24917/20801653.331.13
|View full text |Cite
|
Sign up to set email alerts
|

Przemiany w sferze usług turystycznych Krakowa i ich wpływ na percepcję turystyki przez mieszkańców

Abstract: Miasta dziedzictwa kulturowego UNESCO należą do wiodących destynacji turystycznych na świecie. Kraków jest jednym z przykładów tego typu miast. Celem podjętych badań było poznanie postrzegania wzrostu ruchu turystycznego w Krakowie przez mieszkańców i usługodawców turystycznych oraz ustalenie ich postaw wobec zachowań turystów. Przeprowadzono badania ankietowe z mieszkańcami (677) i wywiady z usługodawcami turystycznymi (50). Mieszkańcy i usługodawcy turystyczni dostrzegają zarówno pozytywny, jak i negatywny w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(22 reference statements)
0
2
0
1
Order By: Relevance
“…The age group 20 to 39 years somewhat dominate the population of tourists, especially foreign tourists, visiting the studied cities. This group of tourists tends to be focused on a superficial examination of the cultural heritage of a city via the sightseeing of only main tourist attractions and an affinity for entertainment and the pursuit of the so-called climate of the city (Colomb & Novy 2017;Tracz et al 2019). Research has shown that younger visitors in Budapest and Prague prefer pubs, bars, clubs and discos, while older visitors prefer cultural venues and restaurants (Dumbrovská & Fialová 2018;Pinke-Sziva et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The age group 20 to 39 years somewhat dominate the population of tourists, especially foreign tourists, visiting the studied cities. This group of tourists tends to be focused on a superficial examination of the cultural heritage of a city via the sightseeing of only main tourist attractions and an affinity for entertainment and the pursuit of the so-called climate of the city (Colomb & Novy 2017;Tracz et al 2019). Research has shown that younger visitors in Budapest and Prague prefer pubs, bars, clubs and discos, while older visitors prefer cultural venues and restaurants (Dumbrovská & Fialová 2018;Pinke-Sziva et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the area has started undergoing the tourismification, gentrification [115], and commodification processes. These have incited a discussion on the ongoing center's depopulation, disturbances caused by the constant city users' and tourists' circulation, and the night-time economy, both in the local media [116][117][118] and among academics [16,114,115,119]. Although the issues have been addressed in the city's latest strategic documents [113,120], the operationalization of the general action frameworks remains the burning question.…”
Section: The Conflict Situation In Krakowmentioning
confidence: 99%
“…Migracja ekonomiczna mieszkańców Grupy V4 do UE wpłynęła na wzrost turystyki związanej z wizytą u krewnych i znajomych. Ponadto miasta te oferują atrakcyjną i stosunkowo tanią ofertę turystyczną (Widawski, Wyszkowski, 2012;Tracz, Bajgier-Kowalska, Wójtowicz, 2019;Więckowski, Saarinen, 2019). Podsumowanie W świetle przeprowadzonych badań można wysunąć kilka wniosków.…”
Section: Dyskusjaunclassified